PERAN ORMAS ISLAM DAN LEMBAGA PENDIDIKAN ISLAM DALAM MEWUJUDKAN MODERASI ISLAM DI INDONESIA - Rachmatullah Rusli; Adam Sugiarto (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
The rise of violence in the name of religion is in stark contrast to the presence of religion which functions to provide peace and tranquility for individuals and the people who adhere to it. In Indonesia, as a country with the largest Muslim population in the world, it has the same problems as the problems of Muslims in general in the world, namely violence in the name of religion. The role of Islamic mass organizations as a forum for Muslims to express their religion is very important in overseeing the process of Islamic moderation to counteract the development of extremist views, and avoid conflicts in the name of religion. In addition, educational institutions also have a very strategic role in instilling the values ​​of moderation in the curriculum and programs for students to avoid extreme views that have the potential to result in violence in the name of religion. This research method uses literature review from analysis of journals related to the role of Islamic organizations of educational institutions in realizing Islamic moderation in Indonesia.